Role of MNREGA to Eliminate Poverty From India - Kumar, Vikas (Journal of Commerce and Trade, 2014)
The poverty alleviation programmes of the Ministry of Rural Development are designed to act as safety nets to the poor during the times of crisis even while addressing partly the multi-dimensional poverty. The National Rural Employment Guarantee Act 2005, a social protection programme, has emerged as a major theme in development discourses perhaps due to its scale of finance and adoption of ‘rights’ based framework. What has been its overall impact and in particular on rural poverty? The effect of MNREGS would be positive for these farm households if the community and individual works undertaken under the scheme help in productivity enhancement of agriculture. Field evidence needs to be systematically analyzed before drawing conclusions of the programme impact.